Ten‐Day Quadruple Therapy Comprising Proton‐Pump Inhibitor, Bismuth, Tetracycline, and Levofloxacin Achieves a High Eradication Rate for Helicobacter pylori Infection after Failure of Sequential Therapy. Issue 1 (6th September 2013) - Hsu, Ping‐I; Chen, Wen‐Chi; Tsay, Feng‐Woei; Shih, Chih‐An; Kao, Sung‐Shuo; Wang, Huay‐Min; Yu, Hsien‐Chung; Lai, Kwok‐Hung; Tseng, Hui‐Hwa; Peng, Nan‐Jing; Chen, Angela; Kuo, Chao‐Hung; et al.
Abstract Background Sequential therapy has been recommended in the Maastricht IV/Florence Consensus Report as the first‐line treatment for Helicobacter pylori eradication in regions with high clarithromycin resistance. However, it fails in 5–24% of infected subjects, and the recommended levofloxacin‐containing triple rescue therapy only achieves a 77% eradication rate after failure of sequential therapy. Aim To investigate the efficacy of a novel quadruple therapy comprising proton‐pump inhibitor, bismuth, tetracycline, and levofloxacin for rescue treatment of sequential therapy. Methods This was a multicenter study in which H. pylori‐infected patients who had failed sequential therapy received a 10‐day quadruple therapy (esomeprazole (40 mg b.d), tripotassium dicitrato bismuthate (120 mg q.d.s.), tetracycline (500 mg q.d.s.), and levofloxacin (500 mg o.d.) for 10 days). H. pylori status was examined 6 weeks after the end of treatment. Results From July 2007 to June 2012, twenty‐four subjects received 10‐day quadruple therapy. The eradication rates according to intention‐to‐treat and per‐protocol analyses were both 95.8% (23 of 24; 95% confidence interval, 87.8–103.8%). Adverse events were seen in 25.0% (6 of 24) of the patients. Drug compliance was 100.0% (24/24). Conclusions The 10‐day quadruple therapy comprising proton‐pump inhibitor, bismuth, tetracycline, and levofloxacin achieves a very high eradication rate for H. pylori infection after failure of sequential therapy. It is well tolerated and has great potential to become a good choice of rescue treatment following non‐bismuth‐containing quadruple therapy in regions with high clarithromycin resistance.